Electric conductance response on engineering properties of heavy metal polluted soils. Issue 4 (August 2018) - Chu, Ya; Liu, Songyu; Wang, Fei; Bian, Hanliang; Cai, Guojun
Abstract: Electrical conductivity measurements provide potentially powerful tool for estimation of physical parameters of heavy metal contaminated soil, which is on the rise in the whole world with the boost of industrialization and urbanization. The main objective of this study is to demonstrate the correlation between electric response of heavy metal contaminated soil and the engineering parameters (Atterberg limits, particle size distribution, ionic concentration and pH), which is an important indicator of site engineering investigation. Laboratory investigations were performed on three heavy metals contaminated soils (zinc, cadmium and lead) with different concentrations. It is found that the mobility of electrical charge in soil is highly affected by water and the diffuse double layer (DDL) at particle surface, which will highly affect the engineering properties of soil. On the basis of the test results, theoretically based models, which capture the intrinsic connections between the surface conductivity and physicochemical properties and is simple enough to be applied in the field, are established. In consequence, surface conductivity is a potentially well adapted alternative method for determination of the physical parameters of heavy metal contaminated soil.